PENGARUH LITERASI KEUANGAN DAN PERILAKU KEUANGAN MAHASISWA TERHADAP MINAT INVESTASI MAHASISWA FAKULTAS EKONOMI DAN BINIS UNIVERSITAS TEKNOLOGI SUMBAWA - Nuraini; Irawati (Jurnal Nusa Manajemen, 2026)
This Study aims to determine (1) the effect of financial literacy on invesment interest of students of the faculity of economics and bussines university of tecnology sumbawa, (2) the effect of financial behavior of students on invesment interest of students of the faculity of economics and bussines university of tecnology sumbawa, (3) determine the effect of financial literacy and financial behavior of students on invesment interest of students of the faculity of economics and bussines university of tecnology sumbawa. The study used an asosiative quantitative method with a population of active students of the faculity of economics and bussines university of tecnologi sumbawa in the 2025/2025 academic years, with a sampel 150 respondents . the sampling tecnique used was Stratified Random Sampling, with a data collection method tha was distributing questionnaires offline and analysis using multiple linier regresion using an analysis tool namely STATA MP 17. The result of the study showed (1) financial literacy had a positive and significant effect on investment interest of students, (2) financial behavior of students had a positive and significant effect on investment interest of students, (3) financial literacy and financial behavior of students had a positive and simultaneous effect on investment interest of students.